Synergies of Extracellular Vesicles and Microchimerism in Promoting Immunotolerance During Pregnancy - Murrieta-Coxca, José M.; Fuentes-Zacarias, Paulina; Ospina-Prieto, Stephanie; Markert, Udo R.; Morales-Prieto, Diana M. (Frontiers in Immunology, 2022)
The concept of biological identity has been traditionally a central issue in immunology. The assumption that entities foreign to a specific organism should be rejected by its immune system, while self-entities do not trigger an immune response is challenged by the expanded immunotolerance observed in pregnancy. To explain this “immunological paradox”, as it was first called by Sir Peter Medawar, several mechanisms have been described in the last decades. Among them, the intentional transfer and retention of small amounts of cells between a mother and her child have gained back the attention. These microchimeric cells contribute to expanding allotolerance in both organisms and enhancing genetic fitness, but they could also provoke aberrant alloimmune activation. Understanding the mechanisms used by microchimeric cells to exert their function in pregnancy has proven to be challenging as per definition they are extremely rare. Profiting from studies in the field of transplantation and cancer research, a synergistic effect of microchimerism and cellular communication based on secretion of extracellular vesicles (EVs) has begun to be unveiled. EVs are already known to play a pivotal role in feto-maternal tolerance by transferring cargo from fetal to maternal immune cells to reshape their function. A further aspect of EVs is their function in antigen presentation either directly or on the surface of recipient cells. Here, we review the current understanding of microchimerism in the feto-maternal tolerance during human pregnancy and the potential role of EVs in mediating allorecognition and tropism of microchimeric cells.